Translation dictionaries triangulation - Simões, Alberto (2010)
Probabilistic Translation Dictionaries (PTD) are translation resources that can be obtained automatically from parallel corpora. Although this process is simple, it requires the existence of a parallel corpora for the involved languages. Minoritized languages have a limited amount of available resources. For example, while they can have a few parallel corpora, the number of parallel language-pairs uses to be restricted. We defend that if a minoritized language A has a parallel corpus with a language B, and language B has a parallel corpus with another language C, then we can obtain a helpful probabilistic translation dictionary between A and C. In this document we will formalize the probabilistic translation dictionaries triangulation, perform some experiments making the triangulation between Galician, English and Italian, and conclude with an evaluation of the proposed approach.